2008
DOI: 10.1080/13545700801986571
|View full text |Cite
|
Sign up to set email alerts
|

Altruism in individual and joint-giving decisions: What's gender got to do with it?

Abstract: This paper uses dictator experiments to examine gender differences in altruistic behavior in the United States when decisions are made individually and jointly. In anonymous individual giving to charity, women give substantially more than men, and in paired settings, mixed-sex groups give the most while all male pairs give the least. Evidence supports social information and negotiation effects as participants change giving toward that of their partners. Social image effects are found only in mixed-sex groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 40 publications
1
35
2
Order By: Relevance
“…It appears that courtesy to females in FM team is token: it increases the likelihood of donation, but not the amount donated. Our results contrast with those of Kamas et al (2008), who found greater effect of social image in the male-female mixed environment and concluded that both males and females become more altruistic in the presence of opposite gender. Again, it appears likely that these differences are due to cultural norms governing cross-gender interactions.…”
Section: Women Solicitors Elicit More Charitycontrasting
confidence: 85%
See 2 more Smart Citations
“…It appears that courtesy to females in FM team is token: it increases the likelihood of donation, but not the amount donated. Our results contrast with those of Kamas et al (2008), who found greater effect of social image in the male-female mixed environment and concluded that both males and females become more altruistic in the presence of opposite gender. Again, it appears likely that these differences are due to cultural norms governing cross-gender interactions.…”
Section: Women Solicitors Elicit More Charitycontrasting
confidence: 85%
“…Gender is among one of the consistent determinants of charitable behavior; relevant literature shows that females in general are usually more generous in charitable giving than males (Leslie et al 2013;Einolf 2011;Mesch et al 2011;Kamas, Preston, and Baum 2008;Piper and Schnepf 2008;Mesch et al 2006). A few of the studies also find that females are more generous in that a greater proportion contributes, but when they donate, men donate more (Piper and Schnepf 2008).…”
Section: Gender and Incomementioning
confidence: 90%
See 1 more Smart Citation
“…Hoogendoorn, Oosterbeek, and van Praag (2013) randomly assign 550 undergraduate business students in Amsterdam to course project groups and find that mixed-gender groups display more intense mutual monitoring and produce better outcomes in a business-oriented scenario. Kamas, Preston, and Baum (2008) look at a group of 164 undergraduate students playing a "dictator" game in which they must split a sum of money between themselves and the American Red Cross. Women tend to give more than men, and a two-person male-female team gives more than the expected sum of what they would give playing alone.…”
Section: Why Economists Should Care About Diversitymentioning
confidence: 99%
“…20 Moreover, recent empirical research supports the increasing role that women overall play in economic and philanthropic decisionmaking. 21 Furthermore, according to a commentary on Jewish women's philanthropy written by Susan Weidman Schneider, "partnership is the model for most Jewish couples." 22 Jewish women make independent financial decisions and influence their husbands' giving decisions.…”
Section: Jewish Philanthropymentioning
confidence: 99%